2018
DOI: 10.1200/jgo.2016.008557
|View full text |Cite
|
Sign up to set email alerts
|

Interfraction Variation and Dosimetric Changes in Patients With Cervical Cancer Treated With Intracavitary Brachytherapy

Abstract: PurposeIntracavitary brachytherapy is integral in the treatment of cervical cancer. Because of interfraction variation, the current standard is replanning with every fraction. This study aimed to determine whether there was a difference in relative dosimetry if the source position and dwell time of the first fraction were applied to subsequent fractions.Materials and MethodsThe authors performed a retrospective review of charts and films from 2007 to 2012. Eligible cases were patients with cervical cancer trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Garipagaoglu et al showed a significant variation in the interfraction position of applicators accounting for different doses delivered to the bladder and rectal tissues, but with no remarkable differences in the radiobiological effective doses 11 whereas the study by Jason et al in his recent retrospective review of 29 patients, showed evidence of the safely considering the first plan using the same source position and dwell time for the subsequent fractions but however do not currently recommend it as a standard of care. 12 This study with a sample size of 133 patients, convey that when the source position and dwell time of the first implemented fraction plan when applied to the subsequent second and third brachytherapy applications, there is a statistically significant difference between the doses received to the point B, rectum and bladder points, which necessitates replanning for every session of brachytherapy. The results of this study is in accordance to the current American Brachytherapy Society recommendation for replanning with every fraction.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Garipagaoglu et al showed a significant variation in the interfraction position of applicators accounting for different doses delivered to the bladder and rectal tissues, but with no remarkable differences in the radiobiological effective doses 11 whereas the study by Jason et al in his recent retrospective review of 29 patients, showed evidence of the safely considering the first plan using the same source position and dwell time for the subsequent fractions but however do not currently recommend it as a standard of care. 12 This study with a sample size of 133 patients, convey that when the source position and dwell time of the first implemented fraction plan when applied to the subsequent second and third brachytherapy applications, there is a statistically significant difference between the doses received to the point B, rectum and bladder points, which necessitates replanning for every session of brachytherapy. The results of this study is in accordance to the current American Brachytherapy Society recommendation for replanning with every fraction.…”
Section: Discussionmentioning
confidence: 90%
“…Jason et al in his recent retrospective review of 29 patients, showed the proof of safely considering the first plan for the subsequent fractions using same source position and dwell time but however do not currently recommend it as a standard of care. 12 Our study aimed to determine the correlation of interfraction variations in positioning of applicator and its relationship with relative dosimetry if the dwell time and source positions of the plan of first fraction were applied to other subsequent fractions.…”
Section: Introductionmentioning
confidence: 99%